L-3-n-Butylphthalide attenuates neuroinflammatory responses by downregulating JNK activation and upregulating Heme oxygenase-1 in lipopolysaccharide-treated mice. Issue 3 (3rd March 2016) - Zhao, Chun-Yang; Lei, Hui; Zhang, Yu; Li, Lin; Xu, Shao-Feng; Cai, Jie; Li, Ping-Ping; Wang, Ling; Wang, Xiao-Liang; Peng, Ying
Abstract: Microglia activation-induced neuroinflammation contributes to neuronal damage in neurodegenerative diseases. Inhibition of microglia activation and reduction of major neurotoxic cytokines have been becoming a therapeutic strategy for neurodegenerative diseases. L-3-n-Butylphthalide (L-NBP) has shown the potent neuroprotective effects in stroke and Alzheimer's disease animal models. The present study investigated the immune modulatory effects of L-NBP on pro-inflammatory cytokines and microglia activation in brain tissue induced by systemic lipopolysaccharide (LPS) treatment in C57BL/6 mice. Our results showed that systemic LPS treatment induced microglia activation in the brain. L-NBP treatment significantly suppressed the expression of proinflammatory cytokines, such as tumor necrosis factor (TNFα), interlukin-1β (IL-1β), interlukin-6 (IL-6), and interlukin-10 (IL-10) in LPS-treated mice. At the meantime, L-NBP treatment decreased the morphological activation of microglia. In addition, the phosphorylation level of JNK MAP kinase-signaling pathway was also inhibited by L-NBP in LPS-treated mice. Furthermore, L-NBP upregulated the expression of heme oxygenase (HO)-1, a key element in the anti-inflammation and anti-oxidative stress. These results suggested that L-NBP might be a promising candidate in delaying and reversing the progress of neurodegenerative diseases by inhibiting microglia activation.